(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2000)
Discussing the forms of the avant-garde, and debating its failure based on the crystallization of these forms is a sine qua non condition for putting the 20s on the table. In Argentina, these years show a complex intellectual field where the patricidal gesture towards the old portraits of established writers (Gálvez, Rojas, and Lugones) is complemented by the debate about the operations to install the new as a cultural category.